DIVERSITY AND BIOMASS POTENTIAL OF UNDERWATER PLANTS AMPUPU PLANTATION FOREST (Eucalyptus urophylla) IN TOKOLULI, RAILAKO DISTRICT ERMERA MUNICIPALITY, TIMOR-LESTE - Leopoldino V. Martins; Mohammad Ali Mahmudi; Neti; Abdul Mukti; Muhammad Rizky Pratama (PT. Pustaka Cendekia Publisher, 2025)
The objective of this study is to determine the composition and diversity of vegetation in the forest planted in Ampupu and determine the biomass and carbon storage of vegetation in the village of Tokoluli, district of Railako, Ermera regency. The population in this study is composed of all types of undergrowth found under teak stands in the village of Tokoluli, Railako district, Ermera regency. The samples in this study are all types of undergrowth contained in the plot or observation plot. The results of the research obtained the highest value of the density parameter from the results of the analysis, the iber, Langur feathers (Rubiaceae) with a total density of 8.466 Ha individual, For the highest relative density value was found in langur feathers (Rubiaceae) of 423.33%, the highest frequency value of all types of subplant plants, namely langur feathers (Rubiaceae) with a value of 8.47, a high important value index shows that the species has the largest number of individuals, the density and frequency of its species found in the community are also high of the 29 species identified, there are several types of undergrowth that have the highest NPI, including langur feathers (Rubiaceae) of 846.7 and caterpillar (Brachiaria decumbens) 193.3, From the results of the analysis of the data, specimens with the highest value of SDR are of the property of the female (Mimosa pudica) 98% and of the Tembelekan (Lantana chambera Linn.) At 98.9%. Some of the types that are also the most valuable SDRs after Tembelekan and Putri Malu with 86.7%, Grass Teki with 83.3% and Alang-Alang with 63.3%. Meanwhile, the species that have the lowest SDR values are Bitter Grass and Manon with 90% and 30%, respectively. The total value of H' de vegetation rasteira en forestestas protegidas na vila de Railako, municipal town of Gleno, is 3153.